Building Social Media, in Conjunction with the Brand, to Drive Purchasing Decisions - Majoe, Nampe (Green Publisher, 2025)
This article tells about how social media influences sales levels in online clothing stores, the role of social media in the modern era is very important, with this convenience many marketers utilize digital marketing strategies. In addition to the role of social media, the role of brands is needed for purchasing decisions on each product marketed on online media. This study uses a quantitative method by distributing questionnaires to 100 customer respondents. The results of the study showed a positive and significant influence on purchasing decisions based on social media and product brands.